2020
DOI: 10.3389/fneur.2020.510800
|View full text |Cite
|
Sign up to set email alerts
|

Soccer-Related Concussions Among Swedish Elite Soccer Players: A Descriptive Study of 1,030 Players

Abstract: Objective: There are growing concerns about the short-and long-term consequences of sports-related concussion, which account for about 5-9% of all sports injuries. We hypothesized there may be sex differences in concussion history and concussion-related symptoms, evaluated among elite soccer players in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…53,104 In a study of more than 1000 Swedish soccer players, about 35% experienced a concussion, of whom 10% were during the last season. 104 And 12 of 40 soccer players with evident white matter integrity only had a history of subconcussive head impact. 79 That raises the question whether soccer players, without symptomatic concussion,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,104 In a study of more than 1000 Swedish soccer players, about 35% experienced a concussion, of whom 10% were during the last season. 104 And 12 of 40 soccer players with evident white matter integrity only had a history of subconcussive head impact. 79 That raises the question whether soccer players, without symptomatic concussion,…”
Section: Discussionmentioning
confidence: 99%
“…96,101 A higher risk of persisting symptoms (headache, fatigue), and worse performance on neuropsychological testing is observed in soccer players with a history of previous concussion. 97,[102][103][104] If the symptoms of the soccer player combined with video-analysis suggest a concussion, there are specific diagnostic tools to substantiate the diagnosis: the Standardized Assessment of Concussion can be used directly, 103 the Sport Concussion Assessment Tool (SCAT5) is applied off-field. 105…”
Section: Diagnosismentioning
confidence: 99%
“…For example, in an experimental study in adult male rats given two traumatic head impacts, separated by either 24 h or 3 days [72], when the second mTBI was given during the first injury cerebral glucose metabolism recovery (CMRg) period (24 h) it prolonged the CMRg dysfunction and animal behavioural impairments compared to the longer time interval. It may take up to a week or more for symptoms to resolve following a concussion [73]. Merchant-Borna et al [74] developed a series of exposure metrics for an epidemiological study of American Football players based on a weighting of PLA and other measures of head impact by the inverse of the time between hits and/or the time interval from hit to post-season health assessment.…”
Section: Discussionmentioning
confidence: 99%
“…13,[25][26] In some cases, athletes who sustain multiple untreated concussions may have poorer long-term outcomes and can be vulnerable to persistent symptoms such as memory loss and depression over 20 years after ending their careers. [27][28] The role of factors such as age, sex, and genetic makeup in concussion incidence and recurrence are not fully understood. 24,29 Neidecker et al showed that female adolescent athletes have a longer duration of symptoms following first-time concussion compared to male athletes, with women remaining symptomatic for a median of 28 days compared to 11 days for their male counterparts.…”
Section: Discussionmentioning
confidence: 99%